Spices research - A crystal gazing - Ravindran, P N (Journal of Spices and Aromatic Crops, 2000)
The direction of research on spice crops especially black pepper (Piper nigrum) and cardamom (Elettaria cardamomum) during the present century has been conceptualized. The revolution that is likely to be created by genetic engineering and biotechnology in the areas of germplasm conservation, crop improvement, crop protection, crop management and postharvest technology, resulting in tremendous increase in productivity of spices has been highlighted.